The Role of Standardisation Initiatives in Local Industrial Development: The Chinese Ginseng Experience. Issue 3 (3rd July 2021) - Kwak, Jooyoung; Lee, Heejin; Han, Sukhee
ABSTRACT: China's emergence in international standardisation has led scholars to debates over its intensifying techno-nationalism. This paper examines ginseng standardization using interviews and archives. Standardisation on the ginseng production started in low-income regions, which later changed into the techno-nationalism agenda over the product origin. Upon international standardisation, the sales volume and unit price in ginseng production increased. Yet the effects occurred in the domestic market and the market leader countries moved to the premium segment by product differentiation. The ginseng standard initiative did not achieve the commercial dominance in the global market but was a local development policy tool.